VERTEX TRIGGERING USING TIME DIFFERENCE MEASUREMENTS IN THE ZEUS CENTRAL TRACKING DETECTOR - Harnew, N; Heath, G; Jeffs, M; Nash, J; Salmon, G; Shield, P; White, D; Wilson, F (1989)
A method of vertex triggering which uses a time difference measurement to determine the z coordinate of a track is under development for the ZEUS Central Tracking Detector. This incorporates a pipelined readout system. We describe the system and report on its performance. © 1989.